Insulin resistance in the retina: possible implications for certain ocular diseases - Zheng, Zhaoxia; Yu, Xiaobing (Frontiers in Endocrinology, 2024)
Insulin resistance (IR) is becoming a worldwide medical and public health challenge as an increasing prevalence of obesity and metabolic disorders. Accumulated evidence has demonstrated a strong relationship between IR and a higher incidence of several dramatically vision-threatening retinal diseases, including diabetic retinopathy, age-related macular degeneration, and glaucoma. In this review, we provide a schematic overview of the associations between IR and certain ocular diseases and further explore the possible mechanisms. Although the exact causes explaining these associations have not been fully elucidated, underlying mechanisms of oxidative stress, chronic low-grade inflammation, endothelial dysfunction and vasoconstriction, and neurodegenerative impairments may be involved. Given that IR is a modifiable risk factor, it may be important to identify patients at a high IR level with prompt treatment, which may decrease the risk of developing certain ocular diseases. Additionally, improving IR through the activation of insulin signaling pathways could become a potential therapeutic target.